Dissecting the Role of Adnp in Neurogenesis Using the Mouse Retina as a Model System - Medisetti, Suma (Université d'Ottawa / University of Ottawa, 2023)
The ADNP (Activity dependent neuroprotective protein) gene encodes a transcription factor that is essential for embryonic development and brain formation. Mutations within this gene cause a neurodevelopmental disorder known as Helsmoortel-Van Der Aa syndrome. ADNP is one of the most commonly mutated single genes associated with autism spectrum disorder. However, its role in neurodevelopment is unclear. Our goal in this study is to dissect the role of Adnp in neurogenesis using the mouse retina as a tractable model system. We hypothesized that Adnp might have a crucial role in retinal neurogenesis. We found that Adnp was consistently expressed in all progenitor cells throughout retinal development. Interestingly, Adnp expression was relatively high in differentiated cells and persisted in the adult retina. Adnp was found to regulate retinal size, possibly by controlling cell survival during retinal development. In the retina, Adnp was found to interact with the Chd4 chromodomain helicase protein and might therefore be involved in chromatin remodelling. On the other hand, it also interacted with Pogz – a zinc finger protein associated with heterochromatin and might have a specific role in neural gene regulation. Altogether, these findings indicate that Adnp plays a crucial role in retinal neurogenesis and identify possible neurodevelopmental mechanisms that might depend on Adnp.
Keywords: Adnp; Neurogenesis; ASD